2009
DOI: 10.2169/internalmedicine.48.1884
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mood Disorders in Japanese Patients with Medication-Overuse Headache

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…In this study, although the difference was not significant, we found that MOH patients who had MO as primary headaches were slightly more common than MO patients in the migraine group. Furthermore, the frequency of comorbidity with depression was higher in MOH patients than in migraine patients [3][4][5]. We also confirmed that the prevalence of depression was significantly higher in MOH patients than in migraine patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, although the difference was not significant, we found that MOH patients who had MO as primary headaches were slightly more common than MO patients in the migraine group. Furthermore, the frequency of comorbidity with depression was higher in MOH patients than in migraine patients [3][4][5]. We also confirmed that the prevalence of depression was significantly higher in MOH patients than in migraine patients.…”
Section: Discussionsupporting
confidence: 81%
“…Although most patients return to the episodic migraine pattern after drug withdrawal, the complications of MOH markedly decrease the quality of life of patients [1]. Furthermore, in contrast to migraine patients, the percentage of comorbidity with depression in MOH patients is higher [3][4][5]. Therefore, it is important to prevent the complications of MOH in patients with migraines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the polymorphisms of SOD (rs4880) [9] and GPX1 (rs1050450) [10] genes have also been implicated in major depression. Previous studies revealed a higher percentage of comorbidity with depression in MOH patients than in migraine patients [11,12] . We also reported that the experience of depression is significantly more frequent in MOH patients than in migraine patients [15] .…”
Section: Discussionmentioning
confidence: 80%
“…In addition, SOD (rs4880) [9] and glutathione peroxidase-1 (GPX1, rs1050450) [10] polymorphisms have also been implicated in major depression which is recognized as a risk factor for the development of MOH in migraine patients [11,12] . However, to the best of our knowledge, there have been no studies on the relationship between antioxidant enzyme gene polymorphisms and MOH.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complication of MOH markedly decreases the quality of life of these patients [1]. In addition, the incidence of comorbidity with depression is higher in MOH patients than in migraine patients [3,5]. Therefore, the aggravation of migraines due to medication overuse needs to be prevented.…”
Section: Introductionmentioning
confidence: 99%